Thoughts: fun and humor in pricing. Issue 5 (19th October 2018) - Liozu, Stephan
Abstract Pricing a function traditionally associated with analytics, finance, or accounting. As such it is often considered as "cut and dry" with little room for humor and fun. Because of the high level of complexity in the pricing discipline, scholars and practitioners alike recommend change management and change leadership in order to increase adoption and assimilation of pricing practices. The goal is primarily to create user's emotional connection with pricing in order to convince them to change. Humor and fun are tools that can help with this positive emotional connection and to make pricing changes viral in an organization.